The Effect of Emotional Intelligence, Individual Characteristics and Job Satisfaction on Employee Performance of Samarinda State Agricultural Polytechnic - Susanto, Agus; Hidayati, Tetra; ZA, Saida Zainurossalamia (Asian Journal of Management Analytics, 2024)
This research focuses on factors that affect the employee’s performance in Samarinda State Agricultural Polytechnic. The factors are emotional intelligence, individual characteristics, and job satisfaction. The Structural Equation Modeling (SEM)-Partial Least Square (PLS) method was used in this study to analyze complex relationships between variables. It can be concluded that there is a direct effect in which emotional intelligence has a positive influence on job satisfaction, while individual characteristics do not have a significant effect on job satisfaction and employee performance. However, job satisfaction itself has a positive and significant influence on employee performance. While there was indirect effect. emotional intelligence and individual characteristics have an indirect effect on performance through employee job satisfaction. These results were obtained from the results of testing 7 hypotheses.  This study provides important insights into the factors that influence employee performance in Samarinda State Agricultural Polytechnic especially emotional intelligence, individual characteristics, and job satisfaction.